DEEP BITE CORRECTION BY INCISORS INTRUSION WITH CONNECTICUT INTRUSION ARCH - case report - Trpevska, Vesna; Tanatarec, Ivan; Srbinoska, Daniela; Cadikovska, Elizabeta (Journal of Morphological Sciences, 2021)
Deep overbite as one of the most common malocclusion that can occur along with other associated malocclusions can be treated with several mechanisms. One such mechanics is true intrusion of anterior teeth. Deep overbite correction by intrusion of anterior teeth affords a number of advantages and is the desired treatment option for gummy smile correction, esthetics improvement as well as correction of mandible rotation in order to improve vertical dimension and to correct Class II malocclusion. This case report describes the orthodontic treatment of a 17-year-old patient diagnosed as severe Angleâ€™s Class II malocclusion with maxillary prognathism and skeletal deep bite, dental Class II division 1 malocclusion associated with 4 mm overbite, an increased overjet and excessive gingival display on smiling. After the analyses and due to the fact that the patient avoided surgical method for her malocclusion correction, our treatment plan in this case was alternative (camouflage) with upper premolars extraction. In the first phase we did 9 mm canine retraction with preserved vertical dimensions of upper incisors. In the second phase of our treatment we did incisor intrusion and en masse retraction of the incisors. Intrusion of upper incisors was done using a 0.017 Ã— 0.025 Connecticut intrusion arch and 0.019 x 0.025 stainless steel as base archwire was used. Outstanding results were achieved with an improved facial profile, smile harmony and stable occlusal relationships. Through this case report we highlight the efficiency of Connecticut intrusion arch as Ð° clinically manageable biomechanical system to optimize the orthodontic treatment. The use of good biomechanical principles helped us to achieve all treatment goals and objectives with minimal side effects. Keywords : deep bite, maxillary incisors intrusion, Connecticut intrusion arch https://doi.org/10.55302/JMS2142135t